Antibiotic resistance and characterisation of Salmonella Typhimurium isolated from chicken from slaughtering house - Elias, Aishah; Shahimi, Safiyyah; Mohd Zaini, Nurul Aqilah; Mutalib, Sahilah; Ariffin, Ahmad Azuhairi (Universiti Putra Malaysia, 2024)
Salmonella is one of the major food pathogens in the broiler industry. Subtyping of Salmonella is critical to monitor and trace its existence in chicken processing lines. Therefore, the present work evaluated the antibiotic resistance and characterisation of Salmonella Typhimurium isolated from the chicken slaughterhouse. A total of 1,100 colonies of tentative Salmonella were isolated and identified using biochemical tests and polymerase chain reaction (PCR). From these 1,100 colonies, 474 were identified as Salmonella spp., while 18 were S. Typhimurium. Antibiotic resistance against nine types of antibiotics was examined for the 18 isolates of S. Typhimurium, namely amoxicillin (10 µg), ampicillin (10 µg), chloramphenicol (30 µg), gentamicin (10 µg), penicillin (10 µg), streptomycin (10 µg), sulfamethoxazole (25 µg), tetracycline (30 µg), and vancomycin (30 µg). It was found that these isolates were resistant to at least four antibiotics or more, while the multiple antibiotic resistance (MAR) index value was 0.64. All S. Typhimurium isolates were resistant to amoxicillin, ampicillin, penicillin, and vancomycin, followed by tetracycline (55.6%, n = 10/18), gentamicin (44.4%, n = 8/18), chloramphenicol (38.9%, n = 7/18), streptomycin (27.8%, n = 5/18), and sulfamethoxazole (11.1%, n = 2/18). A total of 12 antibiograms were observed; A1 - A12. Plasmid’s size ranged from 3 to > 24 kbp, and seven plasmid profiles (P1 - P7) were observed, while Enterobacterial repetitive intergenic consensus-polymerase chain reaction (ERIC-PCR) showed 12 ERIC-PCR fingerprinting (E1–E12). GelCompar II software discriminated the S. Typhimurium into four clusters and five single isolates at 80% similarity. The antibiogram, plasmid profiling, and ERIC-PCR fingerprinting revealed significant genetic heterogeneity in S. Typhimurium strains indicating that consumers could face high contamination risk from consuming chickens obtained from the studied slaughterhouse.